Potential food safety risks in tomato value chains in urban settings of Eastern Ethiopia: a qualitative investigation - Amenu, Kebede; Megersa, Bekele; Jaleta, Megarsa Bedasa; Dinede, Getachew; Worku, Hable; Kasim, Kemal; Taha, Mukerem; Ibrahim, Abdulmuen M.; Kedir, Jafer; Mego, Lina; Roesel, Kristina; Roothaert, Ralph; et al. (Frontiers in Sustainable Food Systems, 2023)
The value chains of tomatoes in Ethiopia are largely informal which may pose potential food safety risks. VCs mapping was carried out with emphasis on tomatoes in two major cities in eastern Ethiopia -Harar and Dire Dawawhich were assessed to identify practices likely to result in unsafe food, considering production, transportation, retail, preparation, and consumption.Methods: Qualitative methods were used to map the VCs to understand the flows, actors, and practices.Group discussions and key informant interviews were performed to better understand the processes, practices, beliefs, and food safety risks in these VCs.The two cities are supplied by two vegetable VCs: the first and larger being from distant producers in central Ethiopia, and the second from surrounding rural and peri-urban producers. The longdistance VCs involve producers, brokers, transporters, wholesalers, retailers, and consumers. The local producers, however, bring their fresh products directly to the cities without the involvement of VC actors other than final retailers and consumers. The study suggests microbiological contamination risks along tomato VCs, potentially including soil contamination, use of sewerage-contaminated irrigation water, untreated manure, unhygienic handling and storage conditions, and dirty contact surfaces during transportation and retailing. Tomatoes are mostly harvested by hand picking, collected, and sorted on the ground exposing to sunlight and physical bruising with potential contamination. More importantly, tomatoes are widely consumed raw without "a kill-step" that certainly contributes to food-borne infections. Suggestions by study participants for improving food safety and hygiene include funding towards improved infrastructure and facilities in the sectors, supporting VC actors with improved technology for quality production, and increasing awareness of good and hygienic practices. Consumers were particularly concerned about contamination with agrochemicals without much emphasis on the potential microbial contaminants. Fresh tomatoes are prepared in a variety of ways and are often consumed raw or slightly cooked. Further recommendations included using health extension workers to conduct awareness campaigns on improved food safety and hygienic practices.The qualitative VC mapping generated useful information for designing intervention strategies, especially targeting developing food safety interventions and an awareness communication campaign.